Q. 7 D4.8( 4 Votes )

# Write each of the following in the simplest form:

Answer :

Assume x = tanθ

= tan^{–1}

= tan^{–1}

= tan^{–1}

= tan^{–1}

= tan^{–1}

Cos θ = 1 – 2 sin^{2} and sinθ =

⇒ 1 – cosθ = 2 sin^{2}

= tan^{–1}

= tan^{–1}

= tan^{–1}(tan)

=

But θ = tan^{–1}x.

∴

Therefore, the simplification of given equation is

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Inverse Trigonometric Functions - 0161 mins

Inverse Trigonometric Functions - 0242 mins

Inverse Trigonometric Functions - 0339 mins

Inverse Trigonometric Functions - 0438 mins

Questions Practice of Inverse trigonometric Functions30 mins

Interactive Quiz | Graphs of inverse trigo functions39 mins

Graphs of inverse trigo functions48 mins

Functions - 0152 mins

Functions - 1047 mins

Functions - 0558 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Prove the following:

**OR**

Prove the following:

Mathematics - Board Papers

Solve the following equation for x :

Mathematics - Board Papers